Provence and the British Imagination (di/segni, 2014)
Although it resonates today with lavender fields, sunny heritage locations and the gentrified memory of Paul Cézanne’s pictorial turbulence, Provence has not always been the attractive territory of pacified leisure and festival culture. since the seventeenth century, indeed, the region has inscribed its shifting geography, complex politics and the extraordinary diversity of its land and seascapes in the perception and imagination of British visitors. in the steps of anonymous or excellent travellers, the chapters of this volume chart some of the most significant moments in the intercultural transactions between the proud linguistic and literary distinctiveness of the province on one hand and the always challenged and sometimes baffled perception of anglophone (and anglophile) visitors on the other. spanning across two centuries, from the largely unknown pre-revolutionary Provence visited by John locke and tobias smollett through the Victorian paradise of popular tourism and finally to the more secret ‘homeland’ of Modernists, this volume reveals an unexpected Provence which, in oblique and complex ways, has long hold a mirror to British culture and often acted as the laboratory of its artistic life.